Quality of care for people with chronic kidney disease: a systematic review and meta-analysis - Ketema, Daniel Bekele; Wallace, Hannah; Hailu, Workagegnehu; Badve, Sunil V; Ronksley, Paul; Neuen, Brendon L; Pecoits-Filho, Roberto; Gallagher, Martin; Kotwal, Sradha; Perkovic, Vlado; Joshi, Rohina; Jun, Min (BMJ open, 2025)
ObjectivesGuideline-based strategies to prevent chronic kidney disease (CKD) progression and complications are available, yet their implementation in clinical practice is uncertain. We aimed to synthesise the available evidence on the concordance of CKD care with clinical guidelines to identify gaps and inform future CKD care.DesignSystematic review and meta-analysis.Data sources, participants, and outcomesWe systematically searched MEDLINE (OVID), EMBASE (OVID) and CINAHL (EBSCOhost) (to 18 July 2025) for observational studies of adults with CKD reporting data on the quality of CKD care. We assessed data on quality indicators of CKD care across domains that related to patient monitoring (glomerular filtration rate and albuminuria), medications use (ACE inhibitors (ACEIs) and angiotensin receptor blockers (ARBs), statins) and treatment targets (blood pressure (BP) and HbA1c). Pooled estimates (95% CI) of the percentage of patients who met the quality indicators for CKD care were estimated using random effects model.Results59 studies across 24 countries, including a total of 3 003 641 patients with CKD, were included. Across studies, 81.3% (95% CI: 75% to 87.6%) of patients received eGFR monitoring, 47.4% (95% CI: 40.0% to 54.7%) had albuminuria testing, and 90% (95% CI: 84.3% to 95.9%) had BP measured. ACEIs/ARBs were prescribed among 56.7% (95% CI: 51.5% to 62%), and statins among 56.6% (95% CI: 48.9% to 64.3%) of patients. BP (systolic BP ≤140/90 mm Hg) and HbA1c (<7%) targets were achieved in 56.5% (95% CI: 48.5% to 64.6%) and 43.5% (95% CI: 39.4% to 47.6%) of patients, respectively. Subgroup analysis indicated higher rates of proteinuria testing among patients with diabetes (52.2%) compared with those without (31.3%).ConclusionsCurrent evidence shows substantial variation in CKD care quality globally. Guideline-concordant care varied according to quality measures and across patient groups, with gaps in indicators like albuminuria testing. These findings underscore the need for effective quality improvement strategies to address gaps in CKD care, including increased albuminuria testing for risk stratification, together with systematic measures for monitoring care quality.PROSPERO registration numberCRD42023391749.